Mucormycosis in a Renal Transplant Recipient: Case Report and Comprehensive Review of Literature - Tamim Hamdi; Vanji Karthikeyan; George J. Alangaden (International Journal of Nephrology)
Mucormycosis is a rare but devastating infection. We present a case of fatal disseminated mucormycosis infection in a renal transplant patient. Uncontrolled diabetes mellitus and immunosuppression are the major predisposing factors to infection with Mucorales. Mucorales are angioinvasive and can infect any organ system. Lungs are the predominant site of infection in solid organ transplant recipients. Prompt diagnosis is challenging and influences outcome. Treatment involves a combination of surgical and medical therapies. Amphotericin B remains the cornerstone in the medical management of mucormycosis, although other agents have been used. Newer agents are promising.